ON LINE READING RESOURCES IN READING CLASS - Melyann Melani (Universitas Negeri Padang, 2015)
Internet has become an inseparable part of the life of most university students norvadays. They can access internet through cellular phone or wireless facility around campus area. Internet is a source of potential benefit in language classroorn provided that the availability of free teaching and leaming resources that can be used in Reading class. FL readers have a more limited opportunity to develop automaticity in Reading since classroom is the only meaningful place where they are exposed to reading. Automatic process in reading is the outcome of thousands of hours of meaningful input. It is something natural that most of FL readers are struggling and consider reading is difficult and also frustrating to most of them considering the amount of time they spend reading. It will be beneficial that teachers are able to explore free online reading resources as an interesting and accessible tool to provide input and eventually help students to read with better comprehension. This article will, therefore, discuss theoretical background on using on line teaching resources, how and what on line resources are available.